Analisis Pengaruh Motivasi, Perilaku Pemimpin dan Pengembangan Karier terhadap Kinerja Pegawai - Yudi Pratama, Yusuf Ilham; Rusandy, Deby Santyo (Universitas Islam Kadiri, 2025)
This researchaims to: 1) Analyze the influence of motivation, leadership behavior, and career development on the performance of employees in the General Affairs Section of the Regional Secretariat in Blitar Regency, 2) Analyze the effect of motivation on the performance of employees in the General Affairs Section of the Regional Secretariat in Blitar Regency, 3) Analyze the influence of leadership behavior on the performance of employees in the General Affairs Section of the Regional Secretariat in Blitar Regency, 4) Analyze the effect of career development on the performance of employees in the General Affairs Section of the Regional Secretariat in Blitar Regency, and 5) Analyze which factors among motivation, leadership behavior, and career development have a dominant influence on the performance of employees in the General Affairs Section of the Regional Secretariat in Blitar Regency. This research employs a quantitative research approach, which aims to explain the influence between variables through hypothesis testing. The independent variables are X1 = Motivation, X2 = Leadership Behavior, X3 = Career Development Opportunities, and the dependent variable is employee performance (Y). Data collection techniques are conducted through questionnaires and surveys, consisting of primary and secondary data. Subsequently, the data is analyzed quantitatively using statistical models in computer programs, employing descriptive analysis and multiple linear regression analysis. The results of the study indicate that: 1) Motivation, leadership behavior, and career development opportunities each have an influence on the performance of employees in the General Affairs Section of the Regional Secretariat of Blitar Regency, 2) Motivation is the dominant variable influencing the performance of employees in the General Affairs Section of the Regional Secretariat of Blitar Regency, and 3) The performance of employees in the General Affairs Section of the Regional Secretariat of Blitar Regency has largely been supported by their work results meeting the established quality targets, as well as their willingness to work overtime to complete tasks within the set time frame.